Inovasi Budaya Organisasi Publik untuk Meningkatkan Kinerja Pelayanan Publik di Indonesia - Kardina, Mutia; Frinaldi, Aldri (Lembaga Yasin AlSys, 2024)
Public organizational cultural innovation is one of the efforts to improve public service performance in Indonesia. This research aims to examine the concept, practices, supporting factors, and challenges in implementing public organizational cultural innovation. The method used is a literature review by analyzing various relevant sources of literature. The results show that the application of values of integrity, professionalism, teamwork, and customer-oriented approach can improve the indices of public satisfaction, efficiency, and effectiveness of public services. The factors supporting the success of public organizational cultural innovation include leadership commitment, employee engagement, effective communication, and appropriate reward systems. However, the implementation of public organizational cultural innovation also faces challenges such as resistance to change, resource limitations, and bureaucratic complexity. A comprehensive strategy and support from various parties are needed to optimize public organizational cultural innovation in enhancing public service performance in Indonesia.